Morphological Analysis of Composition in Explanatory Texts and Exposition in Indonesian Language Book Class VIII Revised Edition 2017 1 - Widayanti; Mahanda; Arya Anggara; Iis Lisnawati Dzuhriza (The Doctoral Studies Program of Linguistics of Udayana University, 2025)
The research entitled